Resilience-Oriented Optimization of Source-Grid-Load Flexible Resources in Distribution Systems: Review and Prospect - Zhuofei YU; Fei LIU; Ruihuan LIU; Chaofan LIN; Di WU; Houtao SUN; Chen CHEN; Zhaohong BIE (Zhongguo dianli)
The safe operation of power systems is seriously challenged by increasingly extreme natural disasters and malicious attacks. The technology of resilient distribution systems can significantly improve the capabilities of distribution systems in resisting and responding to extreme events and efficiently restoring loads. Meanwhile, with the development of smart grid technology, distribution systems have access to various flexible resources, which can improve the reliability and economy of distribution systems in normal conditions, while the potential for resilience enhancement has not yet been fully uncovered. Therefore, this paper presents a systematic review of the resilience-oriented optimization of flexible resources in distribution systems. The categories and modeling methods of flexible resources on source-grid-load sides, as well as their applications in resilient distribution systems, are reviewed and discussed in detail. Moreover, the research trends in resilience enhancement of distribution systems by using the source-grid-load flexible resources are concluded, which can provide constructive guidance for the future development of distribution systems in China.